PENGARUH KEMAMPUAN KERJA PEGAWAI DALAM MENCAPAI TUJUAN ORGANISASI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA PADANGSIDIMPUAN - Yusditara, Wisnu; harahap, Nirmala Haty; Nurdelila (Jurnal KAFEBIS, 2024)
This study aims to measure the extent to which employee work competence influences the achievement of organizational goals at the Department of Public Works and Spatial Planning in Padangsidimpuan City. The research approach used was quantitative descriptive method with techniques such as correlation analysis, simple linear regression, hypothesis testing (t-test), F-test (simultaneous), and coefficient of determination (R2). The results of the correlation analysis showed a correlation coefficient of 0.509 between variable X (employee work competence) and variable Y (achievement of organizational goals). The calculation of the regression coefficient yielded a constant coefficient of 2.894 and a coefficient for the independent variable (X) of 0.169, resulting in the regression equation Y = 2.894 + 0.169X. The t-test yielded a computed t-value of 3.597, exceeding the tabulated t-value of 2.010, and a significance level (sig) of 0.012, which was lower than 0.05. The F-test yielded a computed F-value of 12.705 and a significance level (sig) of 0.000. Comparing this with the tabulated F-value of 4.05, it can be concluded that the hypothesis is accepted. The coefficient of determination (R2) was found to be 0.428, indicating that 42.8% of the variation in the achievement of organizational goals can be explained by employee work competence. The remaining 57.2% is influenced by other variables not included in this study. In conclusion, this study establishes that employee work competence has a positive and significant influence on the achievement of organizational goals at the Department of Public Works and Spatial Planning in Padangsidimpuan City, accounting for 42.8% of the variance.